2018
DOI: 10.17509/ije.v11i1.9400
|View full text |Cite
|
Sign up to set email alerts
|

Reflective Teaching Toward Efl Teachers’ Professional Autonomy: Revisiting Its Development in Indonesia

Abstract: It has been approximately 25 years that reflective teaching in EFL context, particularly in Asia is being encouraged and reviewed. The notable goal emphasizes the teachers’ role as critical lifelong learners in or outside the classroom to bring about continuous mutual development between them and the surroundings. Although myriad research-based studies have paid attention to the developmental praxis of reflective teaching, scant published articles highlight the progress of its empowerment process and quality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…To support the administration of the research, in addition, reflective teaching method was occupied. As concluded by (Lubis, 2018) reflective teaching would everlastingly foster professional autonomy of the 21 st century pre-and in-service EFL teachers. Thus, it is suggested that a highly-balanced reflective activities be raised and advanced as an optional assessing form in the teaching as it involves personal and social aspects (Astika, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…To support the administration of the research, in addition, reflective teaching method was occupied. As concluded by (Lubis, 2018) reflective teaching would everlastingly foster professional autonomy of the 21 st century pre-and in-service EFL teachers. Thus, it is suggested that a highly-balanced reflective activities be raised and advanced as an optional assessing form in the teaching as it involves personal and social aspects (Astika, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…These include Dumlao and Pinatacan (2019) in Thailand; Gutierrez et al (2019) in Chile; Gungor (2016) in Turkey; Li (2008) in China; Minott (2011) in Cayman Islands; Tosriadi et al (2018) in Indonesia; etc. In general terms, these results are gratifying because reflection is undoubtedly the heart of every professional activity in teaching career (Lubis, 2018), and it is "the central matter in the learning process and it can be described as a pendulation between phenomenon/situation-understandingconclusion/action" (Arnesson & Albinsson, 2019, p.448). Besides, research has proved that reflective teachers are likely to be self-efficacious, who tend to "plan more effective lessons, persist when students face challenges, and search extensively for appropriate strategies and materials to improve student achievement" (Baleghizadeh & Javidanmehr, 2014, p.30).…”
Section: Difficulties In Implementation Of Reflective Teachingmentioning
confidence: 99%
“…It is discovered that the methodology is not simply to feel emotions, but to help connect the issues raised in the movie clips to the students' daily lives recently such as thinking many times before posting publicly personal message on social media when anger erupts or pondering the theoretical feedbacks when the thesis proposal is rejected. Relating to this case, as an effective crossroads between emotions and behavior, self-reflection can encourage change in attitude processes (Lubis, 2018). Naturally, there is still a long way to go even when a specific message reaches the students.…”
Section: Forgiven But Not Forgottenmentioning
confidence: 99%